Impairment of Neutrophil Migration to Remote Inflammatory Site during Lung Histoplasmosis. (29th January 2015) - Medeiros, Alexandra I.; Secatto, Adriana; Bélanger, Caroline; Sorgi, Carlos A.; Borgeat, Pierre; Marleau, Sylvie; Faccioli, Lúcia H.
Abstract : Histoplasma capsulatum ( Hc ) induces a pulmonary disease in which leukotrienes promote activation and recruitment of effectors cells. It is also well-recognized that leukotriene B4 (LTB4 ) and platelet-activating factor (PAF) induce leukocyte recruitment to inflammatory sites. We investigated the impact of pulmonary Hc infection on PMN migration to a remote inflammatory site. Our results show that pulmonary Hc infection impairs LTB4 - or PAF-stimulated PMN recruitment to air pouch. Yet, remote inflammation did not modify PMN numbers in the bronchoalveolar lavage fluid (BALF) of Hc -infected mice. Interestingly, the concomitant administration of PAF and LTB4 receptor antagonists inhibited PMN recruitment to both BALF and the remote site, demonstrating cooperation between both mediators. Along that line, our results show that PAF-elicited PMN chemotaxis was abrogated in 5-lipoxygenase-deficient animals. These results suggest caution in the indiscriminate use of anti-inflammatory drugs during infectious diseases.